Indígenas e quilombolas icamiabas em situação de violência: rompendo fronteiras em busca de direitos - ALEIXO, Mariah Torres (Universidade Federal do Pará, 2017)
This paper tries to understand the situations of violence that indigenous and quilombolas women have faced in their interpersonal relationships and the strategies that they use to support or resist. This dissertation has as empirical base interviews and informal conversations with six indians from four different ethnic groups in the state of Pará and five quilombolas from two quilombola communities, also from Pará. The theoretic contributions are studies on human rights and legal pluralism in the law area, and feminism, gender and diversity in the anthropology area. The protagonists faces violence involving many forms of differentiation, like gender, race/color, ethnicity, class, religion. They have a lot of confront strategies, making more or less use of state law (Maria da Penha Law) in conflict resolution.